Illustrating the Outcomes of Community-Based Research: A Case Study on Working with Faith-Based Institutions - Cresswell, James; Janzen, Rich; Ochocka, Joanna (Engaged Scholar Journal)

(untitled) (University of Saskatchewan, 2020)
Incoming immigrants to places like Canada tend to be religious and thereby have sympathies counter to prevailing secularizing trends that emerge in research praxis. This paper presents an illustrative case study of Community-Based Research (CBR) that starts from the community to be studied. We illustrate how CBR can be an effective tool for engaging community stakeholders in solving community problems when stakeholders are part of faith-based institutions. This is accomplished by drawing on Ochocka and Janzen (2014) and Janzen et al. (2016), who discuss the hallmarks of CBR that we used to structure a case study with The Salvation Army (TSA). This paper focuses on TSA as a religious institution and how CBR supports TSA’s adjustment to enhance its relationships with a community it finds itself serving: newcomers. We first outline the hallmarks of CBR and show how they are expressed in our case study. Second, we extend Ochocka and Janzen (2014) and Janzen et al. (2016) by focusing on the functions of CBR to illustrate further the outcomes that can emerge from this sort of approach and make recommendations for researching with faith-based institutions.